Effect of CaSO4 on hydration and phase conversion of calcium aluminate cement. (10th November 2019) - Son, H.M.; Park, Solmoi; Kim, H.Y.; Seo, J.H.; Lee, H.K.
Highlights: CaSO4 had influenced on hydration and conversion of calcium aluminate cement (CAC). The reduction of strength of CAC specimens was inhibited. The incorporating of CaSO4 inhibited the formation of unstable CAH10 by direct precipitation of ettringite. Abstract: Conversion from metastable phase to stable phase in calcium aluminate cement (CAC) causes volumetric instability, resulting in loss of compressive strength. This study investigated the effect of CaSO4 on the phase conversion of calcium aluminate cement. The specimens with different dosage of CaSO4 were exposed to 60 °C to trigger the phase conversion of CAC after curing at 20 °C for 7 days. Analysis with X-ray diffraction, thermogravimetry, mercury intrusion porosimetry, and scanning electron microscopy were conducted. The incorporation of CaSO4 inhibited the formation of unstable CAH10 by direct precipitation of ettringite. As a result, the reduction of strength of CAC specimens due to the increased pore volume by conversion was inhibited by ettringite and monosulfate formation.